For the Love of Psychoanalysis : The Play of Chance in Freud and Derrida - Rottenberg, Elizabeth (Book collections on Project MUSE., 2019)
This book is about what exceeds or resists calculation--in life and in death. Its two parts and nine chapters highlight, in their coupling of Freud and Derrida (""Freuderrida""), the accidents both in and of psychoanalytic writing, and the philosophical question of what limits the openness of our horizon